Peran Kearifan Lokal dalam Mewujudkan Sekolah Ramah Anak bagi Siswa dari Keluarga Miskin Ekstrem di Balikpapan - Sugianto, Sugianto (Jayapangus Press, 2025)
Balikpapan, as one of the important cities in East Kalimantan, has a wealth of culture and local values ​​originating from various tribes such as Bugis, Banjar, Dayak, Javanese, and others. The purpose of this study is to describe (1) the conditions of the implementation of child-friendly schools (SRA) for extremely poor students of junior high schools in Balikpapan City, and (2) local wisdom of Child Friendly Schools in Balikpapan. This type of quantitative description research, with the research period starting from March 2024 to June 2024. The population in this study were all junior high schools in Balikpapan City, the sample of this study was SMPN 2 Balikpapan, SMPN 4 Balikpapan, SMPN 8 Balikpapan, and SMPN 22 Balikpapan. Data collection techniques based on interviews and documentation in the form of questionnaires. The data analysis technique uses a survey method by changing raw data from the survey questionnaire into meaningful information that can be used for decision making. This involves various steps, from data cleaning, statistical analysis, to data visualization to present the research results more clearly. The research results show that (1) the implementation of child-friendly schools for extremely poor students at Balikpapan Middle Schools was carried out well through a safe environment, mental health and students' cognitive abilities, and (2) the level of local wisdom at Balikpapan Middle Schools was well integrated into learning activities. In conclusion, it is necessary to improve understanding of local cultural content, the lack of local wisdom-based learning media, and the increasingly dominant influence of foreign culture, with the need to improve content on local wisdom of child-friendly schools so that extreme poor students can maintain their mental health.